2012
DOI: 10.1016/j.asjsur.2012.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of major postoperative complications and survival for locally advanced esophageal carcinoma patients

Abstract: Patient body mass index, dysphagia, spirometry, type of surgical technique, and operative time can help predict the likelihood of pulmonary or leak complications after esophagectomy. TNM (Tumor, Node, Metastasis) staging can help predict the overall survival after resection in locally advanced cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Nutrition in patients with EC is often compromised and malnutrition was suggested as a risk factor for AL [5]. We however could not identify a correlation between AL and preoperative hypoalbuminaemia, severe weight loss preoperatively or low BMI.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Nutrition in patients with EC is often compromised and malnutrition was suggested as a risk factor for AL [5]. We however could not identify a correlation between AL and preoperative hypoalbuminaemia, severe weight loss preoperatively or low BMI.…”
Section: Discussionmentioning
confidence: 62%
“…Pulmonary complications and failure of the oesophagogastric anastomotic site remain an important source of postoperative morbidity and mortality, despite a clear trend of decreasing incidences of both morbidity and mortality after oesophagectomy over the past decades. The reported leakage incidence after oesophagectomy ranges from 5% to up to 20%, with cervical anastomosis being more prone to leaks but most often with less leak-associated mortality [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned that preservation of the splenic hiatal route would maintain blood flow to the top of the reconstructed stomach. Sunpaweravong et al [20] mentioned that nutrition in patients with esophageal cancer is often compromised and this information suggested that malnutrition is a risk factor for AL. van Rossum et al [21] mentioned that atherosclerotic calcification of the aorta and right postceliac arteries, which supply the gastric tube, is an independent risk factor for AL after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the standard treatment for esophageal cancer is surgery, the frequency of serious complications and the death rate related to surgery are higher than those of other digestive organ cancers . Previous reports have shown that the treatment‐related mortality rate from thoracic esophageal cancer surgery is 3.8–7.9% . Radiotherapy alone has been used to treat elderly patients, those with medically inoperable cancer, those with generalized poor functional capacity, and patients who decline surgery.…”
Section: Introductionmentioning
confidence: 99%